High-performance aluminum alloy, preparation method and application
By adding Ce and La during the aluminum alloy smelting process, Al11Ce3 and nano La2O3 particles are generated, the grains are refined and the grain boundary bonding energy is enhanced, the problem of difficulty in synergistic optimization of strength and toughness in new energy vehicles is solved, and the preparation of high-performance aluminum alloys is realized to meet the performance requirements of new energy vehicle components.
Patent Information
- Application Number
- CN202510563671.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-30
- Publication Date
- 2025-07-15
AI Technical Summary
The existing 6-series aluminum alloys are difficult to optimize their strength and toughness in new energy vehicles, resulting in insufficient reliability of materials under complex working conditions, limiting their in-depth application in the field of new energy vehicle manufacturing.
Ce alloy is added and heated during the aluminum alloy smelting process, then La alloy is added and electromagnetic stirred, sonication is followed by casting and solid solution aging treatment. By generating Al11Ce3 and nano La2O3 particles, the grains are refined and the grain boundary binding energy is enhanced, and the strength and toughness are achieved.
It significantly improves the strength and toughness of aluminum alloy, solves the contradiction between strength and toughness, improves the reliability and corrosion resistance of materials, and meets the performance requirements of new energy vehicle components.
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of aluminum alloy manufacturing, and particularly relates to a high-performance aluminum alloy, a preparation method and an application thereof. Background Art
[0002] At present, with the booming development of new energy vehicle manufacturing, lightweighting plays a crucial role in improving the cruising range, optimizing the battery efficiency and enhancing the vehicle controllability. The 6-series aluminum alloy, with its excellent mechanical properties and outstanding processing characteristics, has become a key material in the lightweighting process of new energy vehicles and is widely used in core components such as body frames, battery trays, and motor housings. Its main alloying elements, magnesium (Mg) and silicon (Si), interact with each other to form the Mg2Si strengthening phase, which endows the alloy with good strength and hardness while maintaining a relatively low density. On the basis of ensuring the structural stability of the vehicle, the overall vehicle weight is significantly reduced, laying a foundation for the efficient operation of new energy vehicles. However, with the rapid progress of new energy vehicle technology, the requirements for the performance of vehicle components are becoming increasingly stringent. In practical applications, the 6-series aluminum alloy gradually reveals prominent technical bottlenecks. During the driving process of new energy vehicles, components need to frequently withstand complex and variable stresses, which pose extremely high requirements for the strength and toughness of the materials. However, under the current process, the 6-series aluminum alloy often increases the content of Mg and Si or adjusts the heat treatment process to promote the precipitation of more Mg2Si strengthening phases to improve the strength. However, this process often leads to an imbalance in the internal microstructure of the alloy, resulting in a significant reduction in plasticity and toughness while the strength is increased, making it difficult to achieve the coordinated optimization of strength and toughness. This contradiction between strength and toughness greatly affects the reliability of vehicle components under complex working conditions and restricts the in-depth application and expansion of the 6-series aluminum alloy in the field of new energy vehicle manufacturing. There is an urgent need to develop a high-performance aluminum alloy to solve the problem of difficult coordinated optimization of strength and toughness. Summary of the Invention
[0003] In view of the technical problems existing in the prior art, the present invention aims to provide a high-performance aluminum alloy, a preparation method and an application thereof to solve the dilemma of difficult coordinated optimization of strength and toughness.
[0004] One of the purposes of the present invention is to provide a preparation method of a high-performance aluminum alloy, comprising: Adding a Ce alloy during alloy melting, holding for 20 - 40 minutes to obtain a first alloy liquid; Adding a La alloy to the first alloy liquid and performing refining under electromagnetic stirring to obtain a second alloy liquid; When the second alloy liquid cools down to 680 - 700 °C, ultrasonically treating the second alloy liquid to obtain a third alloy liquid; Casting the third alloy liquid and performing solution aging treatment to obtain a high-performance aluminum alloy.
[0005] Preferably, the high-performance aluminum alloy components by weight percentage include: Si 1.15 - 1.30%, Fe 0.18 - 0.25%, Cu 0.07 - 0.10%, Mn 0.65 - 0.75%, Mg 1.0 - 1.10%, Cr 0.15 - 0.25%, Zn ≤ 0.2%, Ti ≤ 0.1%, Zr ≤ 0.05%, Ce 0.04 - 0.08%, La 0.04 - 0.08%, and the balance is Al.
[0006] Preferably, the Ce alloy added during alloy melting includes: First, melt the pure aluminum ingot to obtain aluminum liquid; When the aluminum liquid is heated to 720 - 740 °C, add aluminum-manganese alloy, aluminum-chromium alloy, aluminum-silicon alloy, aluminum-copper alloy, aluminum-iron alloy, and aluminum-zinc alloy in sequence, stir and melt to obtain intermediate alloy liquid; Cool the intermediate alloy liquid to 700 - 720 °C, add magnesium ingot, stir and melt to obtain initial alloy liquid; Heat the initial alloy liquid to 720 - 740 °C, add aluminum-cerium alloy, stir and melt.
[0007] Preferably, during the heat preservation process, apply pulsed magnetic field treatment, with a magnetic field frequency of 40 - 60 Hz, an intensity of 0.4 - 0.6 T, and apply it once every 4 - 6 s.
[0008] Preferably, adding La alloy to the first alloy liquid includes adding aluminum-lanthanum alloy when the first alloy liquid is heated to 730 - 740 °C.
[0009] Preferably, the refining under electromagnetic stirring includes using an electromagnetic stirring device with a frequency of 20 - 50 Hz and a power of 5 - 10 kW, continuously stirring for 15 - 20 minutes, and simultaneously introducing argon for refining.
[0010] Preferably, the ultrasonic treatment includes using an ultrasonic treatment device with a frequency of 20 - 40 kHz and a power of 0.5 - 1 kW, inserting the ultrasonic probe into the second alloy liquid to a depth of 50 - 100 mm, and the ultrasonic treatment time is 8 - 10 minutes.
[0011] Preferably, the ultrasonic treatment of the second alloy liquid further includes adding Al-5Ti-B and Al-5Zr master alloys to the second alloy liquid to obtain the third alloy liquid.
[0012] The second object of the present invention is to provide a high-performance aluminum alloy prepared by the preparation method as described above.
[0013] The third object of the present invention is to provide an application of the high-performance aluminum alloy as described above in new energy vehicle components.
[0014] The beneficial effects of the present invention: The present invention provides a method for preparing a high-performance aluminum alloy. When melting the alloy, Ce alloy is added first and kept warm for 20 to 40 minutes to obtain the first alloy liquid; Ce reacts with Al preferentially to form Al 11 Ce3 heterogeneous nucleation sites with the phase size stabilized at 200 - 300 nm, eliminating the interference of La on the nucleation and generation of Al 11 Ce3 in the traditional method when Ce and La are added simultaneously, significantly refining the grain size to 20 - 30 μm and improving the alloy strength.
[0015] La alloy is added to the first alloy liquid and refined under electromagnetic stirring to obtain the second alloy liquid; electromagnetic stirring promotes the segregation of La at the grain boundaries, inhibits the precipitation of grain boundary network phases, enhances the grain boundary binding energy, inhibits intergranular fracture, and improves toughness.
[0016] When the second alloy liquid cools down to 680 - 700 °C, the second alloy liquid is ultrasonically treated to in-situ generate nano-La2O3 to obtain the third alloy liquid. The third alloy liquid is cast and subjected to solution aging treatment to obtain the high-performance aluminum alloy. The nano-La2O3 particles hinder the movement of dislocations through the Orowan strengthening mechanism, improving the alloy strength. At the same time, the dispersion distribution of La2O3 particles refines the Al 11 The synergistic effect of Ce3 phase not only increases the total grain boundary area to delay crack propagation but also inhibits dynamic recrystallization by pinning the grain boundaries, increasing the elongation. The multi-scale synergy of the two avoids the inversion contradiction between strength and toughness in the traditional process. Detailed implementation mode
[0017] According to the first aspect of the present invention, a method for preparing a high-performance aluminum alloy is provided, including: Adding Ce alloy during alloy melting and keeping warm for 20 to 40 minutes to obtain the first alloy liquid; Adding La alloy to the first alloy liquid and refining under electromagnetic stirring to obtain the second alloy liquid; When the second alloy liquid cools down to 680 - 700 °C, ultrasonically treating the second alloy liquid to obtain the third alloy liquid; Casting the third alloy liquid and subjecting it to solution aging treatment to obtain the high-performance aluminum alloy.
[0018] In the present invention, Ce reacts with Al preferentially to form Al 11 Ce3 heterogeneous nucleation sites with the phase size stabilized at 200 - 300 nm, eliminating the competition between La and Ce for binding to Al and the interference of La on Al 11The interference in the nucleation of Ce3 forms complex phases. In the present invention, Ce alloy is added first, significantly refining the grain size to 20 - 30 μm and improving the alloy strength. La alloy is added to the first alloy liquid, and electromagnetic stirring promotes the segregation of La at the grain boundaries, inhibits the precipitation of network phases at the grain boundaries, enhances the grain boundary binding energy, inhibits intergranular fracture, and improves toughness.
[0019] When the second alloy liquid cools down to 680 - 700 °C, the second alloy liquid is ultrasonically treated to induce the in-situ generation of nano-La2O3. The nano-La2O3 particles hinder the movement of dislocations through the Orowan strengthening mechanism, improving the alloy strength. At the same time, the dispersion distribution of La2O3 particles refines the Al 11 The synergistic effect of Ce3 phase not only increases the total grain boundary area to delay crack propagation but also inhibits dynamic recrystallization by pinning the grain boundaries, increasing the elongation. The multi-scale synergy of the two avoids the inverse contradiction between strength and toughness in traditional processes.
[0020] At the same time, the nano-La2O3 particles hinder the contact between the corrosion medium and the aluminum alloy matrix by filling microdefects, refining grains, serving as heterogeneous nucleation cores, and improving the passivation film, increasing the corrosion resistance and enhancing the corrosion resistance of the aluminum alloy; In a preferred embodiment of the present invention, the components of the high-performance aluminum alloy include, by weight percentage: Si 1.15 - 1.30%, Fe 0.18 - 0.25%, Cu 0.07 - 0.10%, Mn 0.65 - 0.75%, Mg 1.0 - 1.10%, Cr 0.15 - 0.25%, Zn ≤ 0.2%, Ti ≤ 0.1%, Zr ≤ 0.05%, Ce 0.04 - 0.08%, La 0.04 - 0.08%, and the rest is Al.
[0021] In a preferred embodiment of the present invention, adding Ce alloy during alloy melting includes: First, melt the pure aluminum ingot to obtain aluminum liquid; When the aluminum liquid is heated to 720 - 740 °C, aluminum-manganese alloy, aluminum-chromium alloy, aluminum-silicon alloy, aluminum-copper alloy, aluminum-iron alloy, and aluminum-zinc alloy are added in sequence, stirred and melted to obtain an intermediate alloy liquid; The intermediate alloy liquid is cooled to 700 - 720 °C, and magnesium ingot is added, stirred and melted to obtain an initial alloy liquid; The initial alloy liquid is heated to 720 - 740 °C, and aluminum-cerium alloy is added, stirred and melted.
[0022] In the present invention, the aluminum-cerium alloy includes Al-10Ce master alloy; In the present invention, an Al-10Mn master alloy is added at 720°C and mechanical stirring is carried out; an Al-5Cr master alloy is added at 730°C and high-frequency electromagnetic stirring is carried out; Al-20Si and Al-50Cu master alloys are added in sequence at 740°C and laminar flow stirring is carried out. When the melt temperature drops to 710°C, magnesium ingots are melted, and after standing for 10 min, gentle stirring is carried out to avoid oxidation of Mg.
[0023] In a preferred embodiment of the present invention, a pulsed magnetic field treatment is applied during the heat preservation process. The magnetic field frequency is 40 - 60 Hz, the intensity is 0.4 - 0.6 T, and it is applied once every 4 - 6 s.
[0024] In the present invention, the pulsed magnetic field treatment can inhibit the gravity segregation of Ce in the aluminum melt due to density differences, regulate the size and distribution of the Al 11 Ce3 phase, promote the homogeneous nucleation of the Al 11 Ce3 phase, accelerate the diffusion of impurity elements such as Fe and Si, making them more easily adsorbed and removed by fluxes (such as NaCl-KCl), and reducing the formation of coarse Al3Fe phases.
[0025] In a preferred embodiment of the present invention, the magnetic field frequency is 50 Hz, the intensity is 0.5 T, and it is applied once every 5 s.
[0026] In the present invention, the magnetic field frequency is set to 50 Hz to penetrate the typical melt depth (≤100 mm) to ensure that the magnetic field acts uniformly on the whole melt. The periodic force (period 20 ms) generated by the 50 Hz alternating magnetic field can induce micro-region oscillation of the melt (amplitude 10 - 20 μm), promoting the uniform distribution of the Al 11 Ce3 phase, while avoiding turbulence caused by high frequency (>100 Hz). During the pulse interval, the temperature difference of the melt recovers to <5°C to avoid composition segregation caused by local undercooling / overheating. The intermittent magnetic field reduces the standard deviation of the size distribution of the Al 11 Ce3 phase from ±50 nm to ±20 nm, avoiding phase coarsening caused by continuous magnetic fields.
[0027] In a preferred embodiment of the present invention, adding a La alloy to the first alloy liquid includes adding an aluminum-lanthanum alloy when the first alloy liquid is heated to 730 - 740°C.
[0028] In the present invention, the aluminum-lanthanum alloy includes an Al-10La master alloy; In a preferred embodiment of the present invention, refining under electromagnetic stirring includes using an electromagnetic stirring device with a frequency of 20 - 50 Hz and a power of 5 - 10 kW, continuously stirring for 15 - 20 minutes, and simultaneously introducing argon for refining.
[0029] In the present invention, electromagnetic stirring at 20 - 50 Hz (with a power of 5 - 10 kW and a duration of 15 - 20 minutes) can generate a strong Lorentz force, driving the melt to form a laminar - turbulent composite convection, promoting the directional migration of La atoms to the grain boundary region, while breaking dendrites and homogenizing the Al 11 Ce3 phase distribution, refining the grain size to 20 - 30 μm; simultaneously introducing argon for refining can efficiently remove gases and adsorb and remove Al2O3 inclusions, reducing stress concentration sources. The combination of the two synergistically improves the tensile strength while increasing the elongation rate, achieving the synergistic optimization of strength and toughness.
[0030] In a preferred embodiment of the present invention, the ultrasonic treatment includes using an ultrasonic treatment device with a frequency of 20 - 40 kHz and a power of 0.5 - 1 kW, inserting the ultrasonic probe into the second alloy liquid to a depth of 50 - 100 mm, and the ultrasonic treatment time is 8 - 10 minutes.
[0031] In a preferred embodiment of the present invention, the ultrasonic treatment of the second alloy liquid further includes adding Al - 5Ti - B and Al - 5Zr master alloys to the second alloy liquid to obtain a third alloy liquid.
[0032] In the present invention, after adding Al - 5Ti - B and Al - 5Zr master alloys to the second alloy liquid, TiB2 particles are generated as heterogeneous nucleation cores, significantly refining the solidification structure, enhancing the alloy strength and changing the toughness. The B element stabilizes the TiB2 phase distribution, preventing the coarsening of TiAl3 at high temperatures and ensuring the durability of the refinement effect. Zr forms nano - scale Al3Zr precipitation phases, pinning dislocations and grain boundaries, raising the recrystallization temperature to above 450 °C and significantly improving the creep resistance. TiB2 and Al3Zr form multi - scale strengthening phases (micrometer + nanometer scale), through the synergistic effect of Orowan strengthening and grain boundary pinning, breaking through the strength - toughness inversion contradiction and achieving the simultaneous improvement of tensile strength and elongation rate. Zr can also inhibit the excessive diffusion of Ti, avoiding the agglomeration of TiB2 and ensuring the long - term stability of the refining agent.
[0033] In the present invention, gradient cooling is adopted during casting, maintaining 670 - 690 °C for the first 30 s, and then cooling to 610 - 630 °C at a rate of 15 °C / min, and a pulsed magnetic field is applied during the solidification stage.
[0034] The pulsed magnetic field generates intermittent Lorentz forces, driving the melt to produce periodic flows, breaking the solute enrichment layer at the solidification front and alleviating constitutional supercooling. The vibration of the melt caused by the magnetic field promotes dendrite fracture, and the broken dendrite fragments become new nucleation cores, and the grain size can be refined to less than 1.5 μm.
[0035] Initially, keep the temperature at 670 - 690 °C to control the melt fluidity. 670 - 690 °C is slightly higher than the liquidus temperature of 660 °C of the aluminum alloy, ensuring that the melt fully fills the mold at the initial stage of casting and avoiding cold shuts or shrinkage cavities. The holding stage evenly distributes the crystal nuclei, providing a nucleation substrate for subsequent solidification. Rapid cooling at 15 °C / min can shorten the solidification time, reduce the segregation of solute elements such as Cu and Mg, and avoid the formation of coarse dendrites. When combined with a pulsed magnetic field, rapid cooling can lock the melt convection effect induced by the magnetic field, making the grain orientation show a preferred distribution and improving the fatigue resistance.
[0036] In the present invention, the preparation method of the high-performance aluminum alloy specifically includes: First, melt the pure aluminum ingot, raise the temperature to 730 °C, and skim the surface scum to obtain aluminum liquid; Raise the temperature of the aluminum liquid to 720 °C, add Al-10Mn master alloy, and carry out mechanical stirring; at 730 °C, add Al-5Cr master alloy and carry out high-frequency electromagnetic stirring; at 740 °C, sequentially add Al-20Si, Al-50Cu, Al-20Fe, and Al-10Zn master alloys and carry out laminar flow stirring. When the melt cools down to 710 °C, melt the magnesium ingot, gently stir after standing for 10 min to obtain the initial alloy liquid; raise the temperature of the initial alloy liquid to 720 - 740 °C, add aluminum cerium alloy, stir and melt it, hold for 20 - 40 minutes, and apply pulsed magnetic field treatment during the holding process. The magnetic field frequency is 40 - 60 Hz, the intensity is 0.4 - 0.6 T, and it is applied once every 4 - 6 s to obtain the first alloy liquid; After the first alloy liquid is heated to 740 °C, add Al-10La master alloy, use an electromagnetic stirring device with a frequency of 20 - 50 Hz and a power of 5 - 10 kW, continuously stir for 15 - 20 minutes, and simultaneously introduce argon gas with a flow rate of 2 L / min for refining. Then stand and skim the slag to obtain the second alloy liquid; When the second alloy liquid cools down to 680 - 700 °C, use an ultrasonic treatment device with a frequency of 20 - 40 kHz and a power of 0.5 - 1 kW, insert the ultrasonic probe into the second alloy liquid to a depth of 50 - 100 mm, and carry out ultrasonic treatment for 8 - 10 minutes; Add Al-5Ti-B and Al-5Zr master alloys, assist in dispersion with an electrostatic field, and rapidly cool to 670 - 680 °C to lock the nano-phase distribution to obtain the third alloy liquid; Cast the third alloy liquid, and carry out solution treatment (hold at 535 °C ± 5 °C for 8 hours, water quench) and aging treatment (hold at 175 °C ± 5 °C for 12 hours, air cool) to obtain the high-performance aluminum alloy.
[0037] In the present invention, the solution treatment further includes first heating from room temperature to 350°C at a rate of 10°C / min, starting timing after reaching the target temperature, and holding for 1 hour; the oxygen content in the furnace is <50 ppm (achieved by argon replacement three times) to prevent oxidation and burning loss of Mg element. Record the furnace temperature fluctuation every 15 minutes (which needs to be maintained within the range of 347 - 353°C); after completing the 1-hour holding at 350°C, heat up to 480°C at a rate of 5°C / min; after reaching 480°C, stabilize for 10 minutes, and then start the 2-hour holding timing. During this period, introduce 0.1% SF6 mixed protective gas (with argon as the carrier) every 30 minutes to further inhibit oxidation. Heat up from 480°C to 535°C at a rate of 15°C / min, and immediately start 0.5-hour holding after reaching 535°C, strictly controlling the time error ≤2 minutes. Synchronously turn on the electromagnetic stirring device (50 Hz / 0.3 T) to promote the uniform distribution of solute elements.
[0038] After the holding is completed, quench to 60°C silicone oil medium at a rate of 25°C / s to freeze the supersaturated solid solution. Immediately clean the quenched sample with acetone to remove the residual silicone oil on the surface.
[0039] In the present invention, the three-stage heating solution operation avoids the thermal shock generated by rapid heating and prevents the sample from deforming due to rapid heating. At the same time, by argon replacement in the low-temperature stage, the oxygen content in the furnace is <50 ppm, which can effectively prevent oxidation and burning loss of Mg element, ensure the stability of the alloy composition, and lay a good foundation for subsequent processing. In the medium-temperature stage, oxidation is further inhibited, and the strengthening phases in the alloy are fully dissolved, creating conditions for improving the alloy performance. In the high-temperature stage, it promotes the uniform distribution of solute elements in the alloy. After the holding is completed, quenching to 60°C silicone oil medium at a rate of 25°C / s can quickly freeze the supersaturated solid solution and retain the favorable tissue state formed at high temperature, thereby improving the comprehensive properties such as strength, toughness, and corrosion resistance of the aluminum alloy.
[0040] According to the second aspect of the present invention, there is provided a high-performance aluminum alloy prepared by the preparation method as described above.
[0041] According to the third aspect of the present invention, there is provided an application of the high-performance aluminum alloy as described above in new energy vehicle components.
[0042] Examples Examples 1 to 10 provide a high-performance aluminum alloy. The components by weight percentage include: Si 1.21%, Fe 0.21%, Cu 0.085%, Mn 0.72%, Mg 1.03%, Cr 0.22%, Zn ≤ 0.2%, Ti ≤ 0.1%, Zr ≤ 0.05%, Ce 0.04 - 0.08%, La 0.04 - 0.08%, and the balance is Al.
[0043] The preparation methods of Examples 1 to 9 include: first melting pure aluminum ingots, heating up to 730 °C and skimming the surface scum to obtain molten aluminum; heating the molten aluminum to 720 °C, adding Al-10Mn master alloy, and performing mechanical stirring; heating to 730 °C, adding Al-5Cr master alloy, and performing high-frequency electromagnetic stirring; heating to 740 °C, sequentially adding Al-20Si, Al-50Cu, Al-20Fe, and Al-10Zn master alloys, and performing laminar stirring. When the melt cools down to 710 °C, melt magnesium ingots, gently stir after standing for 10 min to obtain the initial alloy liquid; heating the initial alloy liquid to 730 °C, adding Al-10Ce alloy, stirring and melting, keeping warm for 20 minutes, and applying pulsed magnetic field treatment during the heat preservation process. The magnetic field frequency is 50 Hz, the intensity is 0.5 T, and it is applied once every 5 s to obtain the first alloy liquid; heating the first alloy liquid to 740 °C, adding Al-10La master alloy, using an electromagnetic stirring device with a frequency of 20 - 50 Hz and a power of 5 - 10 kW, continuously stirring for 15 minutes, and introducing argon gas with a flow rate of 2 L / min for refining at the same time. Then stand and skim the slag to obtain the second alloy liquid; when the second alloy liquid cools down to 690 °C, use an ultrasonic treatment device with a frequency of 20 - 40 kHz and a power of 0.5 - 1 kW, insert the ultrasonic probe into the second alloy liquid to a depth of 50 - 100 mm, and perform ultrasonic treatment for 8 minutes; add Al-5Ti-B and Al-5Zr master alloys, assist dispersion with an electrostatic field, and quickly cool down to 680 °C to lock the nano-phase distribution to obtain the third alloy liquid; cast the third alloy liquid, and perform solution treatment (holding at 535 °C ± 5 °C for 8 hours, water quenching) and aging treatment (holding at 175 °C ± 5 °C for 12 hours, air cooling) to obtain a high-performance aluminum alloy.
[0044] In the preparation method of Example 10, gradient cooling is adopted during casting. The temperature is maintained at 680 °C for the first 30 s, and then decreased to 620 °C at a rate of 15 °C / min. A pulsed magnetic field is applied during the solidification stage. For solution treatment, the temperature is first raised from room temperature to 350 °C at a rate of 10 °C / min. After reaching the target temperature, timing starts and the holding time is 1 hour; the oxygen content in the furnace is <50 ppm (achieved by replacing argon three times) to prevent oxidation and burning loss of Mg element. The furnace temperature fluctuation is recorded every 15 minutes (it needs to be maintained within the range of 347 - 353 °C); after the 350 °C holding is completed, the temperature is raised to 480 °C at a rate of 5 °C / min; after reaching 480 °C, it is stabilized for 10 minutes, and then the 2-hour holding time starts. During this period, a 0.1% SF6 mixed protective gas (using argon as the carrier) is introduced every 30 minutes to further inhibit oxidation. The temperature is raised from 480 °C to 535 °C at a rate of 15 °C / min. After reaching 535 °C, 0.5-hour holding starts immediately, and the time error is strictly controlled within ≤2 minutes. The electromagnetic stirring device (50 Hz / 0.3 T) is turned on synchronously to promote the uniform distribution of solute elements.
[0045] After the holding is completed, it is quenched into a 60 °C silicone oil medium at a rate of 25 °C / s to freeze the supersaturated solid solution. After quenching, the sample is immediately cleaned with acetone to remove the residual silicone oil on the surface.
[0046] Other steps and parameters are the same as those in Example 3.
[0047] The Ce content, La content, electromagnetic stirring parameters, ultrasonic treatment parameters and holding time of Examples 1 - 10 are shown in Table 1.
[0048] Table 1 Preparation parameters of Examples 1 - 10
[0049] Comparative Example 1 Comparative Example 1 provides an aluminum alloy. The components by weight percentage include: Si 1.21%, Fe 0.21%, Cu 0.085%, Mn 0.72%, Mg 1.03%, Cr 0.22%, Zn ≤ 0.2%, Ti ≤ 0.1%, Zr ≤ 0.05%, Ce 0.06%, La 0.06%, and the rest is Al.
[0050] The preparation method includes: first melting pure aluminum ingots, raising the temperature to 730 °C and skimming the surface scum to obtain aluminum liquid; The aluminum liquid is heated to 720 °C and Al-10Mn master alloy is added for mechanical stirring; at 730 °C, Al-5Cr master alloy is added for high-frequency electromagnetic stirring; at 740 °C, Al-20Si, Al-50Cu, Al-20Fe and Al-10Zn master alloys are added in sequence for laminar stirring. When the melt temperature drops to 710 °C, magnesium ingots are melted, and after standing for 10 min, it is gently stirred to obtain the initial alloy liquid; The initial alloy liquid is heated to 730 °C, and Al-10Ce alloy and Al-10La master alloy are added, stirred and melted to obtain the first alloy liquid. At the same time, argon gas with a flow rate of 2 L / min is introduced for refining, and then it is left standing and slagged off to obtain the second alloy liquid; When the second alloy liquid cools down to 690 °C, Al-5Ti-B and Al-5Zr master alloys are added and dispersed with the assistance of an electrostatic field to obtain the third alloy liquid; The third alloy liquid is cast, and solution treatment (holding at 535 °C ± 5 °C for 8 hours, water quenching) and aging treatment (holding at 175 °C ± 5 °C for 12 hours, air cooling) are carried out to obtain the aluminum alloy of Comparative Example 1.
[0051] Comparative Example 2 In the aluminum alloy preparation method provided in this comparative example, Ce is not added, and only 0.06% La is added. Other steps are the same as those in Example 3.
[0052] Comparative Example 3 In the aluminum alloy preparation method provided in this comparative example, La is not added, and only 0.06% Ce is added. Other steps are the same as those in Example 3.
[0053] Comparative Example 4 The second alloy liquid is not ultrasonically treated. Other steps are the same as those in Example 3.
[0054] Performance testing Tensile strength, yield strength and elongation: GB / T 228.1-2021 "Metallic materials - Tensile testing - Part 1: Method of test at room temperature".
[0055] Salt spray corrosion rate: GB / T 10125-2021 "Artificial atmosphere corrosion tests - Salt spray tests" Grain size: GB / T 6394-2017 "Methods for determination of average grain size of metals" The test results are shown in Table 2: Table 2 Performance test results of Examples 1 to 10 and Comparative Examples 1 to 4
[0056] From the above data, it can be seen that the high-performance aluminum alloy prepared in Example 3 has a tensile strength of 453 MPa, an elongation of 12.6%, a corrosion rate of 0.61 mg / cm² / day, and the grain size is refined to 22 μm. The main reason is that 11 The Ce3 phase is evenly distributed, La segregates at the grain boundaries, and nano-La2O3 particles are dispersed in the matrix. Compared with Comparative Example 1, the strength and elongation of the high-performance aluminum alloy in Example 3 are significantly improved. In Comparative Example 4, ultrasonic treatment was not applied, and nano-La2O3 was not formed, and the corrosion rate was 53% higher than that in Example 3.
Claims
1. A method for preparing a high-performance aluminum alloy, characterized in that, Including: Adding Ce alloy during alloy melting, keeping warm for 20 - 40 minutes to obtain the first alloy liquid; Adding La alloy into the first alloy liquid and carrying out refining under electromagnetic stirring to obtain the second alloy liquid; When the second alloy liquid cools down to 680 - 700 °C, subjecting the second alloy liquid to ultrasonic treatment to obtain the third alloy liquid; Casting the third alloy liquid and performing solution aging treatment to obtain a high-performance aluminum alloy.
2. The preparation method according to claim 1, wherein The components of the high-performance aluminum alloy include, by weight percentage: Si 1.15 - 1.30%, Fe 0.18 - 0.25%, Cu 0.07 - 0.10%, Mn 0.65 - 0.75%, Mg 1.0 - 1.10%, Cr 0.15 - 0.25%, Zn ≤ 0.2%, Ti ≤ 0.1%, Zr ≤ 0.05%, Ce 0.04 - 0.08%, La 0.04 - 0.08%, and the rest is Al.
3. The preparation method according to claim 1, characterized in that Adding Ce alloy during the alloy melting includes: First melting pure aluminum ingots to obtain aluminum liquid; When the aluminum liquid is heated to 720 - 740 °C, successively adding aluminum-manganese alloy, aluminum-chromium alloy, aluminum-silicon alloy, aluminum-copper alloy, aluminum-iron alloy, and aluminum-zinc alloy, stirring and melting to obtain an intermediate alloy liquid; Cooling the intermediate alloy liquid to 700 - 720 °C, adding magnesium ingots, stirring and melting to obtain an initial alloy liquid; Heating the initial alloy liquid to 720 - 740 °C, adding aluminum-cerium alloy, and stirring and melting.
4. The preparation method according to claim 1, characterized in that, During the heat preservation process, pulse magnetic field treatment is applied, the magnetic field frequency is 40 - 60 Hz, the intensity is 0.4 - 0.6 T, and it is applied once every 4 - 6 s.
5. The preparation method according to claim 1, wherein, Adding La alloy into the first alloy liquid includes adding aluminum-lanthanum alloy when the first alloy liquid is heated to 730 - 740 °C.
6. The preparation method according to claim 1, characterized in that, Carrying out refining under electromagnetic stirring includes using an electromagnetic stirring device with a frequency of 20 - 50 Hz and a power of 5 - 10 kW, continuously stirring for 15 - 20 minutes, and simultaneously introducing argon for refining.
7. The preparation method according to claim 1, characterized in that, The ultrasonic treatment includes using an ultrasonic treatment device with a frequency of 20 - 40 kHz and a power of 0.5 - 1 kW, inserting the ultrasonic probe into the second alloy liquid to a depth of 50 - 100 mm, and the ultrasonic treatment time is 8 - 10 minutes.
8. The preparation method according to claim 1, characterized in that Subjecting the second alloy liquid to ultrasonic treatment also includes adding Al-5Ti-B and Al-5Zr intermediate alloys into the second alloy liquid to obtain the third alloy liquid.
9. A high-performance aluminum alloy prepared by the preparation method according to any one of claims 1 - 8.
10. An application of the high-performance aluminum alloy according to claim 9 in new energy vehicle components.